2003
DOI: 10.1073/pnas.2237184100
|View full text |Cite
|
Sign up to set email alerts
|

Defective lysosomal targeting of activated fibroblast growth factor receptor 3 in achondroplasia

Abstract: Mutations of fibroblast growth factor receptor 3 (FGFR3) are responsible for achondroplasia (ACH) and related dwarfing conditions in humans. The pathogenesis involves constitutive activation of FGFR3, which inhibits proliferation and differentiation of growth plate chondrocytes. Here we report that activating mutations in FGFR3 increase the stability of the receptor. Our results suggest that the mutations disrupt c-Cbl-mediated ubiquitination that serves as a targeting signal for lysosomal degradation and term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 51 publications
7
98
0
Order By: Relevance
“…We have reported previously that activated FGFR3 is degraded in lysosomes and is directed into this pathway by c-Cbl-mediated ubiquitination (19). In fact, we observed that FGFR3 bearing gain-of-function mutations progress through this pathway less efficiently than WT-FGFR3.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have reported previously that activated FGFR3 is degraded in lysosomes and is directed into this pathway by c-Cbl-mediated ubiquitination (19). In fact, we observed that FGFR3 bearing gain-of-function mutations progress through this pathway less efficiently than WT-FGFR3.…”
Section: Discussionmentioning
confidence: 62%
“…The generation of the COS7 stable cell lines has been previously described (19). Because the effective dose of 17-AAG (InvivoGen) is affected by cell number (20), all HEK 293-based cell lines were plated at 2 ϫ 10 5 cells/cm 2 , and RT112 cells were plated at 2.4 ϫ 10 5 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A further dramatic consequence related to SADDAN (and TDII) mutants is that they fail to be turned over. Accordingly, a defect in receptor degradation has been recently described for the achondroplasia mutation (24). Because the du- ration of signaling could be critical for a cellular response, failure in the mechanisms that attenuate receptor signaling or down-regulate receptor transcription (25) may have devastating effects, thus justifying the severity of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of the oncogenic FGFR mutants have been shown to be inefficiently degraded. For example, the constitutively active mutants of FGFR3, K650E and G380R, which are found in bladder, prostate, and testicle cancer, and MM, as well as in skeletal disorders (Table 1), were shown to escape into a recycling pathway, where they accumulated as active receptors with a half-life of about twice that of wild-type FGFR3 (149). Thus, defective endocytosis contributes to the gain of function of these FGFR3 mutants.…”
Section: Impaired Termination Of Fgfr Signalingmentioning
confidence: 99%